Coletânea, vol. 1 - Rosa, Maria Tereza Mazer [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This report presents the processes, purposes, and the final result of a project that consisted in developing a book about the many aspects of fond and enduring memories, and how those can relate to brazilian music. This was made possible after a study on the importance of specific memories, combined with some research on each artists such memories related to, the last mostly done via CDs booklets and online material. Finally, to express those intentions, the book displays some technical information about each artist followed by a lettering composition of one of their songs. As mentioned on its own title, the compilation of said memory/music aspects resulted on this book.

Este relatório apresenta os processos, objetivos e resultado final do projeto, que consiste no desenvolvimento de um livro capaz de abordar os aspectos de memórias afetivas relacionadas à música brasileira. Para tanto, foi feito um trabalho de registro de lembranças e pesquisas, através de um levantamento dos dados de cada artista contido no livro, por meio de encartes dos CDs físicos ou materiais online. Por fim, para a expressão desse estudo optou-se por dispor no material uma ficha técnica de cada intérprete, seguida de um lettering de uma de suas músicas. Como afirma o próprio título, a compilação deste conjunto memória/música resulta neste livro.
Collection, vol. 1
Keywords: Fond memories; Editorial design; Brazilian popular music; Letterings; Design editorial; Memória afetiva; Música popular brasileira; Gilberto Gil; Alceu Valença; Ney Matogrosso; Zé Ramalho; Fagner; Vital Farias; Lenine; Belchior